Alleviating the Neglected Tropical Diseases: Recent Developments in Diagnostics and Detection - Hazra, Satakshi; Patra, Sanjukta (Current Topics in Medicinal Chemistry, 2018)
Background: Neglected tropical diseases (NTDs) are communicable diseases caused by a group of bacteria, viruses, protozoa and helminths prevalent in more than 145 countries that affect the world's poverty stricken populations. WHO enlists 18 NTDs amongst people living in endemic areas having inaccessibility to preventive measures. Steps to reduce the global disease burden of the NTDs need attention at multi-factorial levels. Control programmes, mass drug administrations, transmission checks, eradication surveillances and diagnoses are some of them. The foremost in this list is confirmatory diagnosis. A comprehensive summary of the innovative, high-impact, multiplexed, low-cost diagnostic tools developed in the last decade that helped to meet the needs of users can depict a holistic approach to further evaluate potential technologies and reagents currently in research. Major Advancements: A literature survey based on developing nano-biotechnological platforms to meet the diagnostic challenges in NTDs towards development of a useful point-of-care (POC) unit is reported. However, in order to pave the way for complete eradication more sensitive tools are required that are user-friendly and applicable for use in endemic and low-resource settings. There are various novel research progresses/advancements made for qualitative and quantitative measurement of infectious load in some diseases like dengue, Chagas disease and leishmaniasis; though further improvements on the specificity and sensitivity front are still awaited. Strategies to combat the problem of antimicrobial drug resistance in diagnosis of NTDs have also been put forward by various research groups and organizations. Moreover, the state-of-the-art “omics” approaches like metabolomics and metagenomics have also started to contribute constructively towards diagnosis and prevention of the NTDs. Conclusion: A concrete solution towards a single specimen based common biomarker detection platform for NTDs is lacking. Identifying robust biomarkers and implementing them on simple diagnostic tools to ease the process of pathogen detection can help us understand the obstacles in current diagnostic measures of the NTDs.
Keywords: biosensor